HIPPO signaling resolves embryonic cell fate conflicts during establishment of pluripotency in vivo - Tristan Frum; Tayler M Murphy; Amy Ralston (eLife, 2018)
During mammalian development, the challenge for the embryo is to override intrinsic cellular plasticity to drive cells to distinct fates. Here, we unveil novel roles for the HIPPO signaling pathway in controlling cell positioning and expression of Sox2, the first marker of pluripotency in the mouse early embryo. We show that maternal and zygotic YAP1 and WWTR1 repress Sox2 while promoting expression of the trophectoderm gene Cdx2 in parallel. Yet, Sox2 is more sensitive than Cdx2 to Yap1/Wwtr1 dosage, leading cells to a state of conflicted cell fate when YAP1/WWTR1 activity is moderate. Remarkably, HIPPO signaling activity resolves conflicted cell fate by repositioning cells to the interior of the embryo, independent of its role in regulating Sox2 expression. Rather, HIPPO antagonizes apical localization of Par complex components PARD6B and aPKC. Thus, negative feedback between HIPPO and Par complex components ensure robust lineage segregation.